ANALISIS PENGARUH ENVIRONMENTAL, SOCIAL, AND GOVERNANCE DISCLOSURE SCORE TERHADAP RETURN ON ASSET PERUSAHAAN DENGAN LEVERAGE DAN ASSET TURNOVER SEBAGAI VARIABEL KONTROL (Studi Pada Perusahaan Publik Non-Keuangan di Negara ASEAN Periode 2016 – 2022) - Farhati, Firda Maulidya; Sampurno, R. Djoko; Almadana, Aulia Vidya (Faculty of Economics and Business Diponegoro University, 2024)
ABSTRACT This study aims to examine the effect of Environmental Social and Governance Disclosure Score (ESG_Disc), Environmental Disclosure Score (ENV_Disc), Social Disclosure Score (SOC_Disc), and Governance Disclosure Score (GOV_Disc) on the company's financial performance proxied by Return On Asset (ROA). This study also adds Leverage (Fin_Lev) and Asset Turnover (AST_TO) as control variables. The population used in this study is nonfinancial public companies in ASEAN countries for 7 periods, from 2016 - 2022. The number of samples used was 153 companies taken by purposive sampling method. The analysis method used is panel data regression which is added to the Robust Standard Error procedure to overcome the heteroscedasticity problem in the Fixed Effect Model (FEM). The results showed that ESG_Disc and ENV_Disc had a significant negative effect on ROA. SOC_Disc was found to have a significant positive effect on ROA. GOV_Disc has a positive effect on ROA, but is not supported by statistical significance. In addition, Leverage (Fin_Lev) has no consistent effect on ROA. Asset Turnover (AST_TO) has a significant positive effect on ROA.